The Influence of Resident's Income Level on Rusunawa Perceptions of Satisfaction, Convenience, and Management - Alfianarrochmah, Ilma; Nugroho, Arief Setiawan Budi; Handayani, Tantri Nastiti (Universitas Negeri Yogyakarta, 2022)
The increasing population growth rate causes a city to face the problem of limited land for residential development. Housing is a fundamental demand of the community that must be fulfilled, especially for low-income people. Through the construction of flats named Rusunawa, the government tries to fulfill the demand for decent housing and anticipates the emergence of slum settlements. In its development, there are Rusunawa whose management is not optimal in maintenance which results in unkempt conditions and causes residents to not get satisfaction and convenience in occupying housing. This study aims to analyze the level of satisfaction, the convenience of residents, and the management of Rusunawa. It is based on the income level of residents and identifies strategies for service improvement of Rusunawa management. This study uses primary data to obtain the level of satisfaction, comfort, and management of flats based on income levels. The data collected is preliminary data consisting of data from questionnaires to the residents of the apartments and data from interviews with the Rusunawa management agency. The method in this study uses a mixed method based on qualitative methods with interview techniques and quantitative methods with survey techniques (questionnaires). The results show that there is a significant difference in the level of building convenience based on the income level of the residents of the Rusunawa. The management of the Rusunawa has not reached its maximum goals related to implementing the Rusunawa regulation. Runaway development programs are required, such as providing counseling, participating in social activities regarding environmental care, and conducting socialization with residents, especially the priority aspects of unique flats for low-income communities.